A reliability model for overcurrent relays considering harmonic-related malfunctions. (October 2021) - Farzin, Hossein; Monadi, Mehdi; Fotuhi-Firuzabad, Mahmud; Savaghebi, Mehdi
Highlights: A 32-state Markov model for overcurrent relays considering harmonic impacts. Calculation procedure of Markov model's steady-state probabilities. Appropriate procedures for estimation of the model's transition rates. A four-state classified model to facilitate the application of the detailed model. Identifying the main factors affecting the reliability of OC relays. Comparative analyses between the proposed model and the existing ones. Abstract: The number of harmonic-producing sources is rapidly growing in the power grid due to the increased penetration of power electronic-interfaced resources (such as wind turbines, photovoltaic systems, and energy storage units) and proliferation of nonlinear loads. Many researchers have investigated the effects of non-sinusoidal waveforms on the performance of different types of protective relays, and have reported some harmonic-related malfunctions. This paper presents a detailed Markov model that captures different impacts of harmonics on the reliability of overcurrent relays. In addition to addressing relevant considerations of the previous reliability models, this model accounts for new harmonic-related aspects, such as loss of protection coordination due to harmonic distortion, non-fault disturbances with high harmonic contents that lead to relay maloperation, and human errors during restoration of components after loss of protection coordination. Moreover, a procedure for estimating the model transition rates is presented, and a four-state classified model is introduced which facilitates the application of the proposed reliability model. Furthermore, case studies are provided to demonstrate the application of the proposed model, and identify the main factors affecting the reliability performance of overcurrent relays in harmonic-polluted environments.